Family Support Related To Self-Harm Behavior Of Students Of The Bachelor Of Nursing Study Program - Akhmad Yanuar Fahmi Pamungkas (Nursing Information Journal, 2026)
Self-harm is a psychological disorder that needs serious attention and priority in prevention and treatment of mental health efforts. Self-harm behavior is a high-risk act committed by a group of adolescents than adults. The purpose of this study was to analyze the relationship of family support to self-ham behavior in female students of Bachelor of Nursing Science Study Program. This research design uses a Cross-sectional design, using Purposive Sampling technique. The number of respondents in this study amounted to 46 female students. Data collection through a closed questionnaire distributed using a family support questionnaire and a Self-harm questionnaire.  Data analysis using the chi-square correlation test to determine the relationship between the two variables. The results of family support obtained 19 people (41.3%) were in the moderate family support category, and the results of Self-harm were 26 people (56.5%) respondents were in the mild self-harm category. The results of this study obtained a Pearson Chi-Square value with SPSS 27 of 13.985 with a significance value of p value 0.001 < α = 0.05, it can be stated that there is a relationship between family support and self-harm behavior in female students of Bachelor of Nursing Science Study Program at STIKES Banyuwangi 2024. It can be concluded that the greater the support provided by the family, the less likely someone is to do Self-harm.